The Perceptions of Emergency Medicine Physicians and Trainees Regarding Family Presence During Adult Patient Resuscitation in South African Public Sector Emergency Centres - McAlpine, Nicola Anita (Division of Emergency Medicine, 2020)
Introduction The benefits of family presence during adult resuscitation (FPDR) are well documented in the literature. However, despite apparent value, FPDR is not always practised. The purpose of this study was to evaluate the perceptions of Emergency Medicine physicians and specialist trainees regarding FPDR in South African public sector Emergency Centres. Method A descriptive study was undertaken, using an electronic survey which consisted of both open and closed-end questions. The Survey was distributed via email to 157 Emergency Medicine physicians and specialist trainees in South Africa. The data was collected and subjected to descriptive statistical analysis. Results Most South African Emergency Medicine physicians and trainees did not feel that FPDR interrupted patient care; did not feel it hindered the teams’ productivity; and did not believe it increases complaints about the quality of patient care. Despite this, practice of FPDR was found to be uncommon. Knowledge regarding FPDR guidelines was poor. Discussion The views of South African Emergency Medicine physicians and specialist trainees regarding FPDR is in keeping with other pro-FPDR countries. However, these views do not seem to translate into practice. FPDR education and development of local guidelines are recommended.